Study guides

☆☆

Q: How do you factor 30x squared minus 26x plus 4?

Write your answer...

Submit

Related questions

(13x^2 - 4y)(2x^2 - 5y)

x2 + 26x + 48 = (x + 24)(x + 2)

6xsquared minus 26x minus 5 over 3xsquared minus 15x

(x2 + 26x +) : syntax error.x2 + 26x

(5x + 6)(x + 4)

2(5x - 1)(3x - 2)

(x+6)(X+20)

8x2 + 15 + 26x = 8x2 + 26x + 15 = 8x2 + 20x + 6x + 15 = 4x(2x + 5) + 3(2x + 5) = (2x + 5)(4x + 3)

3x2+26x+16 When factorised: (3x+2)(x+8)

I'm guessing that's 35x^2 + 26x - 16 which factors to (5x - 2)(7x + 8)

.740

(3/4, 0) and (5/2, 0) Solved with the help of the quadratic equation formula.

x2+36x+120 (x+6)(x+20)

8x + 26x - 7 = 34x - 7 = (√34x)2 - (√7)2 = √34x - √7)(√34x + √7)

26x + 9 = 699Subtract 9 from each side:26x = 690Divide each side by 26 :x = 690/26 = 26 and 14/690 = 26 and 7/345 = 26.5385 (rounded)

It is (3x-4)(5x-2) when factored

26x-4 = 25 +4 +4 26x = 29 x= 29/26 or 1.115...

13(2x - 1)

The answer to this equation would be 5. This is a math problem.

8x - 22 = 2x + 28x - 2x - 22 = 2x - 2x + 26x - 22 = 26x - 22 + 22 = 2+ 226x = 24x = 24/6 = 4

3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3

x2+26x = 68 x2+26x-68 = 0 (x+13)2-68 = 0 (x+13)2-169-68 = 0 x+13 = +/- the square root of 237 x = -13 +/- the square root of 237

-26x

38 = 26x - 7x 38 = 19x (38/19) = x 2 = x

I think there's something missing here, but as written that's 26x - 4x^3 which factors to -2x(2x^2 - 13)